If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y+11=17
We simplify the equation to the form, which is simple to understand
3y+11=17
We move all terms containing y to the left and all other terms to the right.
+3y=+17-11
We simplify left and right side of the equation.
+3y=+6
We divide both sides of the equation by 3 to get y.
y=2
| 5(2-x)+4(3x+x)=83 | | 4p+6=2(p+5) | | r+s+rs+s+rs+s= | | 9(0.5x+2)=3(2.25x+27) | | .4w=5 | | 82-3x=15x+22 | | -16x^2-400=0 | | 18-4y=6 | | 5m(4n-9)+4mn-8m= | | 3n+6=-n-6 | | 1.4w=5 | | 5-9x=169-37x | | 6-w=8 | | 5-y=3-2y | | 7x-5.7=6x+8.3 | | 2n-4=n-10 | | 2x+2=3x-63 | | 4(-2+5)=-2(4x+5) | | 2-8(2+7n)=6n+34 | | 2x+20=6x+24 | | -(5y+6)= | | x-27.9=4x | | 5x-7x-15=-2x+8-15 | | 3x-17=98 | | .60(p)=p-32 | | -(3y+4)= | | 7z-2z=30 | | 0.12(y-9)+0.04y=0.14y-0.09(10) | | -5c(c-8c)= | | 2.8x=5.1 | | y/(-4)+5=15 | | 6t-2(5+4t)=5+2t |